Peningkatan visceral adiposity index berhubungan dengan sindrom metabolik remaja obesitas - Fillah Fithra Dieny; Firdananda Fikri Jauharany; A Fahmy Arif Tsani; Deny Yudi Fitranti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
The increased visceral adiposity index associated with metabolic syndrome in obese adolescentsBackground: Metabolic syndrome is a complex risk factor of cardiovascular disease and diabetes mellitus type II. Metabolic syndrome scores are calculated to describe the severity of the risk of metabolic syndrome. Adipose tissue is an independent risk factor for metabolic changes related to metabolic syndrome. One indicator to calculate the distribution and fat function is through the calculation of the visceral adiposity index (VAI).Objective: Analyzing the correlation of VAI with metabolic syndrome score in adolescents in the City of Semarang.Methods: A cross-sectional study of 95 obese adolescents in Semarang City aged 12-17 years who were selected by consecutive sampling method. The inclusion criteria were students aged 12-17 years; subjects were obese based on BMI for age (BMI/U > 95th percentile CDC 2000 curves); not in chronic pain or the care of a doctor; and not on a certain diet. Data collected were waist circumference (WC), blood pressure, fasting blood sugar levels, triglyceride levels, and high-density lipoprotein (HDL) levels. Metabolic syndrome scores are calculated using metabolic syndrome risk score (cMets). VAI is calculated to measure fat distribution and dysfunction. Correlation of VAI with metabolic syndrome and the component was analyzed with the Spearman test.Results: VAI score has a range of 1.8-14.9 with a greater mean in female subjects. The metabolic syndrome score has a range of -5.9 to 6.3 with a greater mean in male subjects. The Spearman correlation test showed a significant relationship between VAI and HDL levels (r=-0.427), triglyceride levels (r=0.914), and metabolic syndrome scores (r=0.439) in male, and HDL levels (r=-0.427), triglyceride levels (r=0.955), WC (r=0.346), and metabolic syndrome scores (r=0.691) in female.Conclusions: VAI has a significant relationship with the metabolic syndrome score which indicates the body's metabolic profile which is getting worse, so the body's metabolic profile can be described from the magnitude of VAI.